2015
DOI: 10.1128/genomea.01152-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Necrotoxigenic Escherichia coli Isolate

Abstract: Here, we present the draft genome sequence of a necrotoxigenic Escherichia coli strain isolated from a patient following a very rapidly evolving, lethal necrotizing fasciitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…NTEC was reported in 4.8% of isolates in our study that is lower than the prevalence 3.49% in diarrheic calves in Iran (Shahrani et al 2014). NTEC is detected in both diarrheic and non-diarrheic animals; thus, there is no clear evidence for its causative role in lamb diarrhea (Bekal et al 2015). Moreover, the combination pattern of cnf2, cdIII, and F17 were found in diarrheic lambs in this study, while this combination pattern was only reported in diarrheic calves previously (Valat et al 2014).…”
Section: Discussioncontrasting
confidence: 69%
“…NTEC was reported in 4.8% of isolates in our study that is lower than the prevalence 3.49% in diarrheic calves in Iran (Shahrani et al 2014). NTEC is detected in both diarrheic and non-diarrheic animals; thus, there is no clear evidence for its causative role in lamb diarrhea (Bekal et al 2015). Moreover, the combination pattern of cnf2, cdIII, and F17 were found in diarrheic lambs in this study, while this combination pattern was only reported in diarrheic calves previously (Valat et al 2014).…”
Section: Discussioncontrasting
confidence: 69%